Świecka kultura muzyczna w średniowiecznej Polsce - Jabłońska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2000)
Music has accompanied every-day life of Polish society for many centuries. Before Christianity came to Poland, music had often appeared on the occasion of some pagan rites, holidays connected with the cycle of nature or family celebrations. From 966 monody was announced as official ones and in the next centuries the count lyrical music is considered to be professional one. The previous musical habits and tradition change into informal current, creating folk music and then townish music. Since the 13-th and 14-th centuries there has been noticed the process of intermingling of the church aesthetics with native creation, pagan rites and customs with Christian tradition and holy festivals. Apart from these we can observe the presence of Czech, Hungarian, Russian, Scandinavian, French and Italian influence throughout the Middle Ages. In such a way, on the ground of various elements, Polish national music has been created. And the development of medieval music has given rise to the Renaissance polyphony. It is necessary to base on written sources, archeological, ethnographical, ethnological and iconographical ones to research on the state of the musical culture of the Middle Ages in Poland. They allow us to distinguish such forms of music as singing – both solo and choral or with accompaniment, dance music, instrumental music which is played with all four groups of instruments. Music accompanied many different moments of peoples life – at court, at churches, in inns or dining rooms, in baths, squares, graveyards and roads, during tournaments, hunting and war. There were kings and princes, trobadours and knights, priest, hunters, rangers, shepherds, scholars and vagrants; there were singers musicians and composers – both amatours and professionals – among those ones who either played or listened to music. And they came from all classes of medieval society.